Ester Prodrugs of Levofloxacin to Prevent Chelate Formation in Presence of Aluminium Ion - Yorinobu Maeda; Yuka Takahashi; Yuki Naika; Takato Maeda; Yuki Otsuka; Yumi Saeki; Saki Otani; Kunihiko Kohama; Yuhzo Hieda; Takeshi Goromaru; Seiji Eto; Teruo Murakami (Tabriz University of Medical Sciences, 2023)
Background: Intestinal absorption of levofloxacin (LFX) is decreased by the concomitant administration of antacids due to the formation of insoluble chelate complexes with various metal cations. Methods: The following four ester prodrugs of LFX-cilexetil ester (LFX-CLX), medoxomil ester (LFX-MDX), ethoxycarbonyl 1-ethyl hemiacetal ester (LFX-EHE) and pivaloyloxymethyl ester (LFX-PVM)-were synthesized. Then, the lipophilicity, in vitro chelate formation with aluminum chloride (AlCl3), chemical and enzymatic stability, minimum inhibitory concentrations (MICs) against some bacteria, and the efficacy in preventing chelate formation of prodrugs with aluminum hydroxide (Al(OH)3) in rabbits were evaluated. Results: The synthesized ester prodrugs of LFX exhibited high purity and higher lipophilicities than LFX depending on the ester moieties. MICs of the prodrugs against S. aureus, E. coli, and P. aeruginosa were more than 10 times higher than those of LFX. Prodrugs were stable chemically but unstable enzymatically and generated LFX in biological specimens. When AlCl3 solution was mixed with LFX solution in vitro, insoluble chelate complex was formed immediately. In rabbits, co-administration of Al(OH)3 with LFX reduced the oral bioavailability of LFX by approximately 40%. In contrast, no precipitation was observed when AlCl3 solution was mixed with each prodrug solution in vitro, and co-administration of Al(OH)3 exerted no significant effect on the oral bioavailability of LFX when each prodrug was administered in rabbits. Conclusion: The ester prodrug approach of LFX could be a feasible strategy for avoiding chelate formation with aluminum ion in vivo.